PENERAPAN KEJUJURAN MELALUI PENDIDIKAN KEWARGANEGARAAN DI SEKOLAH DASAR - Irene May Widiyani Safitrih (Insan Cendekia : Jurnal Pendidikan dan Kebudayaan, 2025)
The key to improving education is honesty. As a result, education seems to ignore a number of problems associated with this initial problem. For that we need a way to reduce it. Teaching Civics in primary schools is a good way to solve this problem. This study aims to teach Civics in elementary schools to help people live honestly. Because it will shape the personality of students, Civics learning in elementary schools is very important in this regard. Meanwhile, this study uses a qualitative approach by reading relevant journals. Opinions about fictional characters. The conclusion of this study is that students learn the importance of character education, including honest behavior, through Civics learning in elementary schools. As a result, students become good citizens.